Оnline university instruction during the Covid 19 pandemic in relation to the domain of education - Јasmina M. Arsenijević; Мilica J. Andevski (University of Belgrade, Teacher Education Faculty, 2022)
The goal of this paper is to examine the difference in dimensions of online university teaching relative to the domain of education. The dimensions of online teaching correspond to the theoretical model of community of inquiry framework developed in the year 2000 by Garrison, Anderson and Archer and comprise teaching, social and cognitive presence. The paper presents an international quantitative research carried out in the school year 2021/2022 and using survey technique among students (N=808) from Serbia, Bosnia and Herzegovina, Croatia, Slovenia, Romania, and Russia. A modified version of an instrument for examining online instruction and its dimensions was applied and tested, while the analysis of the internal consistency of this instrument showed a high level of reliability (α=0,941). The Kruskal-Wallis test demonstrated that there are statistically significant differences among the dimensions of online teaching in relation to the field of education. The highest score is consistently observed in the field of Social sciences and humanities, followed by the field of Engineering and technology, Natural sciences and mathematics, Art and interdisciplinary studies, whereas the lowest scores are observed in the field of Medical sciences. The results indicate the specificities of each educational field that were not recognized and taken into consideration by educational technology in its universal approach, which implies the necessity of creating educational technology that would be relevant for different educational fields, as well as focusing on a combination of online instruction and on-site teaching and learning.